Changes in chemical composition and structure of root cell wall of citrus rootstock seedlings in response to boron deficiency by FTIR spectroscopy. Issue 2 (4th March 2018) - Dong, Xiaochang; Lu, Xiaopei; Wu, Xiuwen; Liu, Guidong; Yan, Lei; Muhammad, Riaz; Wu, Lishu; Jiang, Cuncang
ABSTRACT: Boron (B) is an essential microelement for higher plants, and plays a role in cell wall formation. Citrange seedlings with different amounts of B were studied through Fourier-transform infrared spectroscopy (FTIR) analyses. The results showed that the growth and development of new roots were evidently inhibited by B deficiency. Boron-deficiency significantly increased cell wall biomass (CWB) as a percentage of root fresh weight and the ratio of B concentration in cell wall to the total B in roots. The findings from CWB FTIR spectra showed the band at 3429 cm −1 under control condition was shifted to 3442 cm −1 after being B deprived, suggesting that the mode of hydrogen bonding was changed by B deficiency. Boron deficiency clearly decreased the peak height of carboxylic ester band around 1741 cm −1, but increased that of COO − stretching band around 1400 cm −1, suggesting that the relative amount and degree of esterification of carboxylic groups was decreased and pectin content and structure was altered. These results demonstrate that changes in amount, structure, and assembly of root cell wall polymers may be either specific or adaptive responses of citrange seedlings to B deficiency and FTIR can be an appropriate method to study changes in cell wall under B deficiency.